DAMPAK KEDISIPLINAN DAN KESELAMATAN KERJA OPERATOR FORKLIFT - Muh Kadarisman; Sherly Septirani; Simon Gultom (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2017)
The purpose of this research is to analyze the correlation of forklift operators in compliance with safety regulations at PT. YCH Cibitung. The research used quantitative method with simple regression data analysis. The result of the research shows that there is a significant correlation between disciplines to comply with safety regulation with forklift operators’ safety. Based on the correlation coefficient r = 0.8694, means Discipline to Comply with Safety Regulation (X variable) has strong correlation to Forklift Operators’ Safety (Y variable). The value of coefficient determinant equals to 75.58%, this means contribution of Discipline to Comply with Safety Regulation in forklift operation increases work safety by 75.58%.  The hypotheses testing shows t stat = 9.9514 > t table = 1.6938.  This suggests that there is a significant correlation between Discipline to Comply with Safety Regulation to Forklift Operators’ Safety at PT. YCH Cibitung.